Childhood histoplasmosis in Colombia : Clinical and laboratory observations of 45 patients (2016)
ABSTRACT: Histoplasmosis is an important mycosis in the Americas; and in children with no immune system abnormalities, histoplasmosis is typically a self-limited process. In contrast, in children with immune problems, disease manifestations are frequently more severe and include dissemination. From 1984 to 2010, a retrospective study of paediatric patients who had been diagnosed with histoplasmosis was performed. A total of 45 pediatric cases of histoplasmosis were identified. The most important risk factor was malnutrition (37%), followed by environmental exposure (33%). The patients exhibited pulmonary infiltrates (83%), fever (76%), cough, constitutional symptoms (38%), headache (35%), and lymph node hypertrophy (33%). Concerning the clinical forms, 64% of the patients presented with the progressive disseminated form that frequently affected the central nervous system (48%). Diagnostic laboratory tests indicated that the cultures were positive for 80% of the patients, the agar gel immunodiffusion was reactive in 95%, the M band of the precipitate was more commonly observed (81%), and the complement fixation tests were reactive in 88% of the patients. The timely diagnosis of histoplasmosis is important, and for this reason, it is hoped that the results of this study will lead pediatricians toward a better understanding of this mycosis in children.